2013
DOI: 10.1016/j.jjcc.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation improves outcome compared to open-heart surgery in kidney transplant recipients requiring aortic valve replacement

Abstract: Based on our center's experience, TAVI appears to be an effective and safe alternative to conventional surgery for AVR in patients with prior renal transplantation. Renal transplantation is not currently identified as a risk factor in our traditional scoring system, and may need to be considered independently when weighing alternatives for AVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…As a minimally invasive alternative, TAVI has evolved to become the new standard of care for inoperable patients with severe, symptomatic aortic valve stenosis [9] and to be a viable treatment option for high-risk, but operable patients [10], as recently demonstrated in the Placement of Aortic Transcatheter Valves (PARTNER) trial, and also in patients with previous renal transplantation [11]. In contrast to large aortic valve registries, cohort A of the randomized PARTNER trial presented a somewhat huge number of patients with previous cardiac surgery (42.6% of the TAVI group and 44.2% in the surgical AVR group).…”
Section: Discussionmentioning
confidence: 99%
“…As a minimally invasive alternative, TAVI has evolved to become the new standard of care for inoperable patients with severe, symptomatic aortic valve stenosis [9] and to be a viable treatment option for high-risk, but operable patients [10], as recently demonstrated in the Placement of Aortic Transcatheter Valves (PARTNER) trial, and also in patients with previous renal transplantation [11]. In contrast to large aortic valve registries, cohort A of the randomized PARTNER trial presented a somewhat huge number of patients with previous cardiac surgery (42.6% of the TAVI group and 44.2% in the surgical AVR group).…”
Section: Discussionmentioning
confidence: 99%
“…Even after transplantation, cardiovascular and valvular diseases are still prevalent and remain one of the leading causes of death in kidney transplant recipients ( 57 ). Furthermore, the incidence of AS among kidney transplant patients will likely rise as their survival improves and as the mean age of patients undergoing kidney transplantation increases ( 58 ). Data on the survival of kidney transplantation patients after cardiac valve replacement are limited.…”
Section: Tavr In Kidney Transplant Recipientsmentioning
confidence: 99%
“…Recent data from the US Renal Data System database demonstrated mortality rates of kidney transplant recipients undergoing valvular heart surgery of 14% in the hospital and 40% within 2 years of surgery ( 57 ). In addition, kidney transplant recipients with severe AS are often found unsuitable for SAVR due to impaired kidney function, possible side effects of immunosuppressive medication, and comorbidities ( 58 ).…”
Section: Tavr In Kidney Transplant Recipientsmentioning
confidence: 99%
“…In a study of 8 renal transplant recipients who underwent TAVR prior to transplantation, mortality at 12 months was 0%, with 1 reported cardiovascular event (stroke), compared with 30‐day mortality of 11.2% and 1‐year mortality of 16.7% in patients who underwent surgical AVR (SAVR) 111. Although patients with ESRD were not included in the initial clinical trials evaluating TAVR, case reports have not found any absolute contraindication to TAVR, especially in those who may otherwise be denied renal transplantation 111, 112. In the new 2014 AHA/ACC guidelines for the management of patients with valvular heart disease, TAVR has a class 1 indication for patients who have prohibitive risk for SAVR and post‐TAVR survival >12 months 103.…”
Section: Valvular Disease In Patients With Esrdmentioning
confidence: 99%
“…111 Although patients with ESRD were not included in the initial clinical trials evaluating TAVR, case reports have not found any absolute contraindication to TAVR, especially in those who may otherwise be denied renal transplantation. 111,112 In the new 2014 AHA/ ACC guidelines for the management of patients with valvular heart disease, TAVR has a class 1 indication for patients who have prohibitive risk for SAVR and post-TAVR survival >12 months. 103 TAVR is a reasonable alternative to SAVR in renal transplantation candidates.…”
Section: Transcatheter Versus Surgical Therapy Of Valvular Diseasementioning
confidence: 99%